Između sna i jave / Between Dream and Reality: Može li nam umjetnost vratiti nadu u bolju budućnost / Can arts give us hope for better future - Repovac, Hidajet (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
A speench on monograph (master's thesis) Sculpture as an activity in the life, the spiritual and social world by Samir Sućeska.